Procyclical implications of Basel II: Can the cyclicality of capital requirements be contained? - Andersen, Henrik (Journal of Financial Stability, 2011)
While the current capital adequacy framework, Basel II, aims to make banks’ capital requirements more sensitive to the underlying risk of the assets, it may also introduce an additional source of procyclicality in the banking sector. In this paper we assess the potential cyclicality of Basel II for the entire bank portfolio. This is in contrast to previous studies which have taken into account only parts of banks’ assets, and also neglected the potential cyclicality of bank capital. We apply a detailed data set covering a relatively long period to analyse the cyclicality of both bank capital and Basel II capital requirements. Moreover, we employ a more comprehensive system of models than applied in the existing literature. Consistent with previous evidence, we find a substantial increase in the calculated Basel II capital requirements at the same time as bank capital deteriorates in a recession scenario. However, we also find that the cyclicality of Basel II capital requirements may be effectively contained if risk weightings are based on a sufficiently long observation period which includes economic downturns.